STRUKTUR KOMUNITAS IKAN PADA EKOSISTEM LAMUN DI PANTAI PUDING KABUPATEN BANGKA SELATAN - Sania Prisilia; Wahyu Adi; Arief Febrianto (Akuatik: Jurnal Sumberdaya Perairan, 2018)
Seagrass beds have a variety of roles in fish life, which can be used as nurseries, as a place for feeding ground, and for areas to seek protection. This study aims to analyze the structure of fish communities and seagrass communities and analyze the relationship of fish abundance with seagrass ecosystems. This research was conducted in March 2018 on the beach of Puding Air Banten II, Pasir Putih Village, Tukak Sadai District, Bangka Selatan Regency. Line transect method for seagrass data collection and fish data retrieval using fixed gill nets (gill net). The results of the study found that the total number of individual fish as much as 409 ind / m2 consisted of 25 species. The highest abundance of fish found in Station I with Ambassis interrupta species as many as 241 ind / m2. There were six types of seagrass found on the coast of Puding, namely Enhalus acoroides, Thalassia hemprichii, Halodule uninervis, Halophila spinulosa, Halophila decipiens and Cymodocea serrulata. The highest seagrass density was found at Station I with the seagrass Halodule uninervis species of 2541 ind / m2. Correlation coefficient analysis shows that the abundance of fish with seagrass density has a significant value of 0.956 which is classified as having a very strong relationship. Fish have higher abundance with seagrass meadows which vegetate with mangroves